Practical Approaches for Knock-Out Gene Editing in Pigs - Ratner, Laura Daniela; La Motta, Gaston Emilio; Briski, Olinda; Salamone, Daniel Felipe; Fernandez-Martin, Rafael (Frontiers in Genetics, 2021)
Pigs are an important resource for meat production and serve as a model for human diseases. Due to their physiological and anatomical similarities to humans, these animals can recapitulate symptoms of human diseases, becoming an effective model for biomedical research. Although, in the past pig have not been widely used partially because of the difficulty in genetic modification; nowadays, with the new revolutionary technology of programmable nucleases, and fundamentally of the CRISPR-Cas9 systems, it is possible for the first time to precisely modify the porcine genome as never before. To this purpose, it is necessary to introduce the system into early stage zygotes or to edit cells followed by somatic cell nuclear transfer (SCNT). In this review, several strategies for gene-edited pig production using the CRISPR-Cas system will be summarized, as well as genotyping methods and different delivery techniques to introduce these tools into the embryos Finally, the best approaches to produce homogeneous, biallelic edited animals will be discussed.